Chiral Recognition Mechanism of Benzyltetrahydroisoquinoline Alkaloids: Cyclodextrin-Mediated Capillary Electrophoresis, Chiral HPLC, and NMR Spectroscopy Study - Erzsébet Várnagy; Gergő Tóth; Sándor Hosztafi; Máté Dobó; Ida Fejős; Szabolcs Béni (Molecules, 2025)
The tetrahydroisoquinoline skeleton is a pharmacologically significant core structure containing chiral centers, making enantiomeric separation crucial due to the potentially distinct biological effects of each enantiomer. In this study, laudanosine (N-methyl-tetrahydropapaverine) and its three derivatives (6′-bromo-laudanosine, norlaudanosine, and N-propyl-norlaudanosine) were synthesized and used as model compounds to investigate chiral recognition mechanisms. Screening over twenty cyclodextrins (CyDs) as chiral selectors in capillary electrophoresis (CE), we found anionic CyDs to be the most effective, with sulfated-γ-CyD (S-γ-CyD) achieving a maximum Rs of 10.5 for laudanosine. Notably, octakis-(6-deoxy-6-(2-carboxyethyl)-thio)-γ-CyD (sugammadex, SGX), heptakis-(2,3-O-diacetyl-6-O-sulfo)-β-CD (HDAS), heptakis-(2,3-O-dimethyl-6-O-sulfo)-β-CD (HDMS), and octakis-(2,3-O-dimethyl-6-O-sulfo)-γ-CD (ODMS) provided excellent enantioseparation for all four analytes. Following HPLC screening on CyD-based and polysaccharide-based chiral stationary phases, semi-preparative HPLC methods using amylose and cellulose-based columns were optimized to isolate enantiomers. The purity of the isolated enantiomers was evaluated by HPLC, and their configurations were confirmed via circular dichroism spectroscopy. The isolated enantiomers allowed us to explore enantiomer migration order reversals in CE and enantiomer elution order reversal in HPLC. Further 1H and 2D ROESY NMR experiments provided atomic-level insights into enantioselective complex formation, confirming enantiomer differentiation by SGX and elucidating the inclusion complex structure, where the ring C immersion into the CyD cavity is prevalent.